Thrombolytic-related complication in a case of misdiagnosed myocardial infarction. (June 2014) - Irivbogbe, Osereme; Mirrer, Brooks; Loarte, Pablo; Gale, Michael; Cohen, Ronny
Abstract The importance of early thrombolysis in acute myocardial infarction has been highlighted in several large trials. The clinical decision is often taken by physicians who need to take a rapid action with the risk of misdiagnosing non-coronary events that mimic myocardial infarction. Here we describe a case of acute pericarditis in a 37-year-old man whom received thrombolysis and developed a sudden hemorrhagic pericardial effusion that evolved rapidly into a cardiac tamponade. These errors leading to lethal thrombolysis complications have been surprisingly rare; but a correct diagnosis of aortic dissection or hemorrhagic pericarditis needs to be stressed because even after obtaining the correct diagnosis, the prolonged disturbance of hemostasis prevents a rapid therapy being instigated.